Fabrication and characterization of carbon nanotubes/polydimethylsiloxane nanocomposite for low piezoresistive pressure sensor - Azhari, Saman (2016)
Pressure sensors can vary drastically in technology, design, performance, application suitability and cost. A conventional estimate would be that there may be over 50 technologies and at least 300 companies making pressure sensors worldwide. However considering the number of companies there are still certain range of pressure, scale and applications that are being under developed. Being able to detect pressure at micrometer and nanometer scales would be of an advantage. In recent years conductive and piezoresistive pastes fabricated via nanomaterials are attracting a lot of attention. Polydimethylsiloxane (PDMS) is the most common silicon based organic polymer. Mechanical and electrical properties of PDMS make it an ideal polymeric material for Nano fluidic, wearable and flexible sensory applications. One of the most common issues that are not fully resolved is CNTs tendency to aggregate while being mixed in polymeric matrix. Our goal for this work is to fabricate a homogenous CNTs/PDMS nanocomposite with Piezoresistive properties for applications in flexible electronics and sensory devices. The first step taken in this work is to characterize the CNTs. In this work two common solvents to prepare CNTs/PDMS nanocomposite have been compared. Moreover the electrical properties of samples prepared by solvent mixing and the effect of mixing techniques and curing time on aggregation of CNTs were discussed. Different purification processes and advantages of functional CNTs were studied and functional CNTs were utilized to fabricate a homogenously dispersed CNTs/PDMS nanocomposite. Based on the results obtained, purification of CNTs increases the crystallinity and functionalization enhances the dispersion rate of CNTs in PDMS. There is a direct relation between mixing method and curing time with aggregation rate of CNTs in PDMS; THF displays better dispersion in comparison with chloroform and CNTs/PDMS nanocomposite exhibits measurable conductance at above 10 wt%. Piezoresistive measurements indicate this material could be a suitable replacement for piezoresistive materials used for sensory devices due to their high sensitivity, accuracy and flexibility in addition to their adjustable size.